War and Trade in Maritime East Asia - Oka, Mihoko (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2022)
This book is divided into two parts. One is the state of trade in East Asia before and after the collapse of the tributary system to the Ming Dynasty, and the other is the war of aggression in which Toyotomi Hideyoshi of Japan sent a large number of troops to the Korean Peninsula with a view of conquering China at the end of the sixteenth century. With regard to East Asia in the sixteenth and seventeenth centuries, the contributors in this book share a problem awareness in terms of using trade and war as subjects to clarify multi-ethnic, borderless, and multi-layered situations. Although there are many chapters related to Japan, this book tries to grasp the interaction between Japan as a region of East Asia and neighboring countries from a global perspective, not the one singular national history. Mihoko Oka is an associate professor at the School of Interdisciplinary Information Studies and Historiographical Institute, University of Tokyo.
1. Introduction -- 2. The Meaning of the East Asian Maritime History: From a Japanese Perspective -- 3. The Study of Maritime Asian History in Japanese Schools -- Part I. Picturing Actors on the Sea -- 4. Japanese Daimyōs as Sea Lords in the 15th and 16th Centuries: Their Involvement in the Japan-Ming Trade -- 5. The Origin of the Namban Trade: The Sea of Private Traders -- 6. Sino-Portuguese Negotiation and Collaboration: The Ming Naval Revolt of 1564 -- 7. Edo Period Maps of the Old World: An Analysis on Their Textual Information of Ports and Trade -- Part II. The Japanese Invasion of Korea -- 8. Another Altan Khan in Maritime Asia?: Controversies on the Revival of Sino-Japanese Tributary Trade During the Japanese Invasion of Korea -- 9. Bloody Headcount: A Dispute over Reward and the Mutiny of the Ming Southern Soldiers in the First Stage of the Korea War (1592-1595) -- 10. The Diffusion of Japanese Firearms in the Ming Dynasty at the End of the 16th Century: From the Japanese Invasion of Korea to Yang Yinglong's Revolt in Bozhou -- 11. Repatriation of Korean Captives from Japan after Toyotomi's Invasion.
Keywords: World history; Asia-History.; International trade; World History, Global and Transnational History; Asian History; International Trade